DOES EXPERIENCE MATTER ON EXPORT-PRENEURIAL BEHAVIOURS AND BUSINESS PERFORMANCE? - Ariguzo, Vivian Adaobi, Egwakhe, A. Johnson, & Adefulu, Adesoga (International Journal of Research Science and Management, 2019)
The work argued that foreign market opportunities, firm resources and entrepreneurial ideologies influenced business performance of export firms but queried the exporter experience. Three hundred and ninety-five ownermanagers of selected non-oil export firms were surveyed after selecting them purposively. A validated questionnaire was utilized to collect primary data, after reliability testing was conducted. Hierarchical regression analysis was conducted to determine the moderating effect of export experience on the export-preneurial behaviours and business performance. From the results, the study concludes that export experience does not significantly moderate the relationship between export-preneurial behaviours and business performance. The paper recommends that managers should focus efforts on adaptation and adopting of export-preneurial behaviours in engendering improved business performance.